PENINGKATAN MOTIVASI BELAJAR MENGGUNAKAN MEDIA DAKABI (DADU PERKALIAN PEMBAGIAN) PADA PESERTA DIDIK KELAS III SDN DUKUH KUPANG 1/488 SURABAYA - Dhea Prisca Imanda Agnesa; Diah Yovita Suryarini; Mawan Dwiyanto (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This research aims to determine the improvement in students' learning motivation through the use of Dice media and the Team Games Tournament (TGT) learning model in mathematics subjects, specifically in multiplication and division, in Class III at SDN Dukuh Kupang I/488 Surabaya. The study was motivated by the low level of student motivation observed during learning activities, particularly in mathematics. A Classroom Action Research (CAR) approach was employed and conducted in Class III with a total of 28 students. Data were collected through questionnaires and direct observation during the learning process. The questionnaire data were analyzed using a descriptive quantitative method. The research was implemented in two cycles, each consisting of four stages. The results showed an improvement in students’ learning motivation in mathematics (multiplication and division) when using Sudoku media combined with the TGT model. Based on the analyzed data, there was a 6% increase in motivation from Cycle I to Cycle II, with the motivation levels rising from 82% to 88%. These results indicate that the learning motivation of Class III students at SDN Dukuh Kupang I/488 Surabaya falls into the high category.